Listening Comprehension Orientations and Strategies in Learning English Language: A Review Paper - Sufian Awae; Nur Salina Binti Ismail; Mohammad Halabieh (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2020)
This paper reviews the listening comprehension orientations and strategies in learning English language among L2 learners. Listening skill is one of the most critical key in learning English language. Listening comprehension is a process of understanding the language input in which helps the EFL learners to receive and interact with language input and enables the emergence of other language skills. Heavy research was carried out concerning listening comprehension problems and strategies. Thus, this paper reviews approximately 50 papers with a time span from 2010 to 2019. By searching on Google Scholar and Research Gate for the terms: listening comprehension, listening comprehension orientations, listening comprehension difficulties, and listening comprehension strategies. In general, most studies found that whenever EFL learners face a difficulty in listening, they try to find out the most effective listening strategies to solve their listening difficulties. By doing this, they could improve their listening comprehension. Further research is recommended in order to review papers that dealt with the strategies of other skills i.e. reading strategies and speaking strategies since they are under researched. DOI:https://doi.org/10.5281/zenodo.4033803